PENGEMBANGAN E-LEARNING BERBANTUAN VIRTUAL LABORATORY UNTUK MATA KULIAH PRAKTIKUM FISIKA DASAR II DI PROGRAM STUDI PENDIDIKAN FISIKA FKIP UNSRI - Dwi Agustine; Ketang Wiyono; M Muslim (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2014)
This research has successfully developed E-learning Assisted Virtual Laboratory For Practical Basic Physics II In Program Of Study Physical Education Fkip Unsri which valid, practical and have a potential effect. The method used in this research is a Development Research that use Rowntree model comprising the steps of planning, development and evaluation. The evaluation used is Tesmer formative evaluation consisted of self evaluation, expert review, a one-to-one, small group and a field test. Data collection techniques with walktrough, questionnaires and tests. This research has resulted a valid e-learning assisted virtual laboratory with validation percentage score 91.67 %, of material aspect, 96.75 % of the media aspects and 77.78 % of instructional design aspects. E-learning Assisted Virtual Laboratory For Practical Basic Physics II developed practicality scores at stage one-to-one stage of 81.30 % and 81.50 % for small group are included in the category of very practical. The test results on the field test phase of 44 students who got an A by 31.82 %, the value of B was 34.09 % and the value of C by 34.09 %. Based on the research results, it can be concluded that Development E-learning Assisted Virtual Laboratory For Practical Basic Physics II has a valid, practical and have a potential effect.